2018
DOI: 10.1029/2017ja025161
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Nitrogen Oxide to High‐Speed Solar Wind Stream in the Polar Middle Atmosphere

Abstract: During high-speed solar wind stream (HSS) events, energetic electrons from the Earth's inner magnetosphere transfer solar wind energy to the high-latitude upper atmosphere, which may affect chemical compositions in the region. We conduct a study on the production of nitrogen oxides (NO x ) in the polar middle atmosphere by energetic electron precipitation (EEP) during HSS events in the period of international polar year 2007-2008 northern winter. During this period, the geomagnetic activity was generally quiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The SWS determines the energetic electron flux precipitating from the radiation belts at subauroral latitudes (Tinsley, 2008; Zhou et al., 2014). The analysis of the associations between SW parameters and EEP events showed a positive correlation between the energetic electron flux and SWS, whereas SWS minima were related to minima in EEP precipitating from the radiation belts (Lee et al., 2018; Tinsley et al., 1994; Wilcox et al., 1973; Zhou et al., 2014). According to the results of Asikainen and Ruopsa (2016), SWS is the most important property affecting EEP, and that may explain the short‐term impact of SWS on the NAOI and AOI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SWS determines the energetic electron flux precipitating from the radiation belts at subauroral latitudes (Tinsley, 2008; Zhou et al., 2014). The analysis of the associations between SW parameters and EEP events showed a positive correlation between the energetic electron flux and SWS, whereas SWS minima were related to minima in EEP precipitating from the radiation belts (Lee et al., 2018; Tinsley et al., 1994; Wilcox et al., 1973; Zhou et al., 2014). According to the results of Asikainen and Ruopsa (2016), SWS is the most important property affecting EEP, and that may explain the short‐term impact of SWS on the NAOI and AOI.…”
Section: Discussionmentioning
confidence: 99%
“…In the polar/night stratosphere, it was detected the changes in atmospheric chemistry due to EEP at a weekly timescale. Over high latiiudes (>75°N) in winter, a decrease in total ozone at 30–35 km altitude was observed after EEP events during one week period (Karagodin et al., 2018) and a lower mixing ozone concentration at 30–45 km altitude was observed some days after HSSW accompanied by an increased Ap over 70°N latitudes (Lee at al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the multiyear SOFIE NO data sets (Hendrickx et al, 2015(Hendrickx et al, , 2017(Hendrickx et al, , 2018, combined with model calculations (Smith-Johnsen et al, 2017), suggests that geomagnetic activity is the dominant source of short-term NO variability throughout the high-latitude lower thermosphere, whereas mesospheric NO variability is mainly due to the indirect effect of downward-transported NO originating from~75 km. Lee et al (2018) used Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) data to identify direct NO x production by MEE down to~55 km. A semiempirical model based on MIPAS data sets (Funke et al, 2017) allows computation of EPP-modulated reactive nitrogen (NO y ) species and wintertime downward fluxes through the stratosphere and mesosphere.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The EPP-induced NO x in the polar thermosphere and mesosphere is transported downward within the polar vortex by meridional circulation, contributing to the enhancement of NO x in the stratosphere during polar winter [16][17][18][19][20][21]. It is well known that NO x and HO x are responsible for the catalytic ozone destruction in the polar middle atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Seppälä et al [4] suggested that the ozone destruction by EPP is comparable to the climate forcings by the variations of solar ultraviolet (UV) radiation. More recently, Lee et al [21] reported that NO x can be directly produced at about 55 km altitude during geomagnetic storm periods in association with high-speed solar wind streams using satellite observation data.…”
Section: Introductionmentioning
confidence: 99%